RESEÑA de: Piris, Jean-Claude. "The future of Europe : towards a two speed EU?". Cambridge : Cambridge University-Press, 2012. - Rodríguez-Izquierdo Serrano, Myriam (Teoría y Realidad Constitucional, 2014)
-